Real-World Major Adverse Cardiovascular Events of Nicorandil and Nitrate in Coronary Heart Disease in Central China: A Retrospective Cohort Study - Ping Li; Juan Chen; Na Li; Xiang You; Lan Shen; Ning Zhou (Cardiology Discovery)
Objective:. Residual cardiovascular risk in patients with coronary heart disease (CHD) still needs to be addressed in real-world practice. This study aimed to examine the clinical effectiveness of nicorandil and nitrate in addition to optimal treatment for CHD patients. Methods:. This retrospective cohort study included patients with CHD between October 2009 and March 2020 from 2 tertiary hospitals in Wuhan, China. Patients were grouped into nicorandil and nitrate groups depending on the first recorded antianginal therapy. Demographic and clinical data were collected from databases of the 2 hospitals. The primary outcome was cumulative 18-month major adverse cardiovascular event (MACE)-free survival, which was evaluated by Kaplan-Meier analysis. Propensity score matching (PSM) and multivariate Cox regression were adopted to adjust for confounding factors. Results:. A total of 14,275 patients were analyzed, including 590 and 13,685 patients in the nicorandil and nitrate groups, respectively. With a median follow-up of 0.88 (Q1, Q3: 0.21, 1.54) years, the cumulative 18-month MACE-free survival rates were comparable between the 2 groups (80.0% vs. 75.0%, adjusted hazard ratio (aHR): 1.04, 95% confidence interval (CI): 0.42–2.56, P = 0.982,7) after 1:4 PSM. The cumulative 18-month stroke-free survival rate was significantly higher in the nicorandil group compared to the nitrate group (93.0% vs. 84.0%, aHR: 0.56, 95% CI: 0.34–0.92, P = 0.023,5). Conclusion:. This retrospective study showed that nicorandil and nitrate have similar 18-month rates of MACEs in CHD patients, but nicorandil is associated with lower incidence of stroke compared to nitrate. More studies need to be conducted to validate this association and explore the long-term benefit of nicorandil use on the occurrence of MACEs in the future.